Teaching Practice of Experiencied and New Professors of the Degree General Practitioner of UAS - López Cuevas, Adriana; Ruiz Xicoténcatl, Juan; Mazo Sandoval, María Concepción; Salazar Soto, Dora Yaqueline (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2019)
In the university education is presenting the teaching generational change, the new professors are excellent professionals, but do not know how to teach, it is causing difficulties in the teaching-learning process. The objective was to determine the training needs of novice and experienced professors in the Degree General ´Practitioner in UAS. The methodology was qualitative, descriptive type and socioanthropological approach, in which the Likert survey, interview and observation were used. The results show that the training needs of both professors are in the dimension of teaching, research, time and teacher training.